PENTINGNYA ANALISIS JABATAN DALAM MENINGKATKAN EFISIENSI KERJA DI DINAS PEKERJAAN UMUM DAN PERUMAHAN RAKYAT (PUPR) - Riksa Raesalat; Aceng Ulumudin; Felia Windy Oktaviani (Sawala : Jurnal Administrasi Negara, 2024)
Every government agency requires an effective human resource management system to ensure the availability of qualified employees. This research aims to analyze the implementation of job analysis at the Public Works and Spatial Planning Office (PUPR) of Garut Regency, specifically in the Water Resources Sector. Several identified issues include the failure to collect rainfall data by the UPT in each sub-district, the mismatch between employees' educational backgrounds and job specifications, and the incomplete achievement of some work programs in 2021. This research uses qualitative methods with a descriptive approach through direct observation, interviews with relevant stakeholders, and document analysis at the Garut Regency Public Works and Spatial Planning Office (PUPR). The research results indicate that based on four dimensions of job analysis, several improvement steps are necessary. First, the head of the UPT must be committed to proposing improvements to the rainfall measurement instruments to support performance indicators. Second, the mismatch in employees' educational backgrounds can be addressed through training to enhance competencies or by providing opportunities to pursue higher education. Third, more intensive supervision and in-depth evaluation of program implementation are necessary to improve the quality of field activities